Information society, citizens and everyday life: does the Internet make a difference in spatial practices? - Tommi Inkinen (Fennia: International Journal of Geography, 2003)
The essence of the information society has been under a considerable debate during the last decade. The argumentation concerns the critique of technological determinism and the recognition of political, economic, social and cultural factors that underlie the development. In academic discourse, there has been a noticeable change from engineering based rhetoric towards more humanistic themes and a more qualitative way of speaking about the issue. Also geographical dimensions, mainly related to the urban research and applied urban planning, have emerged. In this paper the essence of the information society is analysed from a perspective of human and cultural geography. The concept of information society is being treated as a subjective construction and it can be conceptualised as a triad. Firstly, it is a tool as such, and the reference is on material symbols representing the tech-sphere of today. This includes actual devices such as computers and mobile telephones and their integrated applications. Secondly, the information society is a set of practices. This refers to everyday routines that are rarely questioned or critically explored. The most common examples of this are e-banking and e-shopping. Finally, the information society is an experience. This theme is characterised by subjective histories, individual contexts and cultural backgrounds. All these dimensions have implications on environment and social conditions of human life. This framework is being used as a tool to evaluate empirical data based on extensive survey conducted in Finland in the year 2001. The sample size was 2750 questionnaires of which 1176 were received back.